Objective Sleep Metrics for Evidence-Based Design of Therapeutic Environments - Ping-Wen Lee; Chih-Hong Huang; Huei-Chen Lin; Ling-Ling Chiang (HERD: Health Environments Research & Design Journal, 2026)
Despite therapeutic environments being increasingly recognized as health determinants for residents with cognitive decline in care facilities, empirical research examining their measurable outcomes objectively for residents remains limited. Objectives: This study explored the potential moderating effects of therapeutic environments in facilities, as assessed by the Environmental Audit Tool (EAT), on sleep quality of residents with either normal cognition or mild cognitive impairment (MCI). Method: A cross-sectional study involving 43 participants (32 cognitively normal and 11 with MCI) was conducted across nine residential care facilities. The cognitive status of participants was evaluated using the Mini-Mental State Examination, and objective sleep measures were obtained through validated actigraphy. Therapeutic environments were evaluated through sensitivity analysis using three a priori EAT total score thresholds: 48, 50, and 52. Comparisons were performed using the Mann–Whitney U test. Results: Participants with MCI exhibited prolonged sleep onset latency, increased wake after sleep onset, and decreased sleep efficiency. The differences observed diminished as the total EAT score increased, and these disparities were largely absent at an EAT score of approximately 50. Residency conditions, including duration of stay, room occupancy, and perceived environmental noise, were significantly correlated with the EAT subscales of visual access, unnecessary stimuli, helpful stimuli, familiarity, privacy and community, and domestic activities. Conclusions: This study examined facility- and individual-level variations in therapeutic environments, highlighting sleep as a design-responsive metric for cognitive resilience, and emphasizing environmental factors such as safety, visual access, familiarity, acoustic control, sensory clarity, and surveillance-privacy balance to improve sleep in residents with MCI.